Congenital Jejunal Diverticular Bleeding in a Young Adult - Ji-Yung Lee; Jae-Young Jang; Min-Je Kim; Tae-In Lee; Jung-Wook Kim; Young-Woon Chang (Clinical Endoscopy, 2017)
Diverticular bleeding of the small bowel is rare and occurs primarily in adults aged more than 60 years. In younger adults, Meckel’s diverticulum, a true diverticulum that congenitally occurs in the distal ileum, is the most common cause of diverticular bleeding of the small bowel. Unlike Meckel’s diverticula, other kinds of small bowel diverticula are not congenital and their incidence is related to age. Furthermore, congenital true diverticular bleeding of the jejunum in adults is very rare. We report the case of a 24-year-old man with subepithelial tumor-like lesion accompanied with obscure overt gastrointestinal bleeding. This lesion was initially suspected to be a subepithelial tumor based on radiologic tests and capsule endoscopy. He was finally diagnosed with a congenital true diverticulum in the jejunum with the appearance of a Meckel’s diverticulum after surgical resection.